IMPROVING STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT BY USING PICTURE STORY - Vira Triana Paputungan; Sarah Kamagi; Rinny Rorimpandey (SoCul: International Journal of Research in Social Cultural Issues, 2022)
The aim of this study is to find out whether the use of picture story is effective to improve students’ reading comprehension, especially using the stories of narrative text. The stories presented are themed local stories in the country (Cerita Rakyat) because students are still not familiar with the story. In this study, the writers adjust to the level of students’ thinking. Therefore, picture story is one of the considerations where this media is able and effective to improve students’ reading comprehension. The approach of this study is quantitative. Multiple Choice and True or False test are used as the instruments eliciting the data. The subject of this study was the seventh grade students of SMP Negeri 5 Bolaang. The result shows that there is an increase between the pre-test (11.85) and the post-test (14.75). This indicates that picture story improve students’ reading comprehension. This is suggested that picture story can be used as effective media in improve students’ reading comprehension.